Does Research and Development Influence Balance of Trade? A Noble GMM-PVAR Analysis - Kumar Debasis Dutta; Mallika Saha; Asif Faysal (ETIKONOMI, 2024)
Research Originality: Research and development expenditure (RDE) is essential for international trade to evolve continuously, especially during the fourth industrial revolution (4IR). Despite this significance, research on RDE and balance of trade (BOT) must be substantially improved. To the best of our knowledge, this study is the first to investigate the RDE-BOT nexus.Research Objectives: This study aims to investigate the causal relationship between RDE and the balance of trade (BOT)Research Methods: Using panel data of 64 countries, we analyse RDE-BOT relationship by employing the generalized method of moment panel vector autoregressive (GMM-PVAR) techniques. Empirical Results: The results show that RDE and BOT affect each other. RDE may initially have a detrimental effect on BOT; however, investment in RDE improves export competitiveness and thereby upholds BOT. Implications: Overall, the findings offer a nuanced understanding of RDE's potential benefits on trade outcomes and guide policymakers seeking to optimize their countries' trade positions in an increasingly globalized and knowledge-intensive economy.JEL Classification: J1, O3How to Cite:Dutta, K. D., Saha, M., Faysal, A., (2024). Does Research and Development Influence Balance of Trade? A Noble GMM-PVAR Analysis. Etikonomi, 23(2), 527 – 538. https://doi.org/10.15408/etk.v23i2.37798.